Um recorte histórico sobre a política de direitos LGBT no Brasil e em Portugal - Moreira Lima, Andréa (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This paperhasas its object of study the social analysis of sexual politics and the construction of LGBT human rights in Braziland in Portugal, having as its locus the cities of Belo Horizonte and Lisbon. The translation of particular demands of the social movement to universal replies construct edby government politic shadbeen investigate dbasedon concrete relational dynamics developed by different social actors, social projects and programmes involved in the construction of the LGBT human rights policy. It has been noticed that, regarding public policies, thetopicis still treated as a politics of minorvalueregarding the otherones, which demonstrate show muchthe naturalization of institutional homophobiadefiesusre garding the rupture with such a sexistlogic.